Prevention and Liquidation of Emergency Situations: Sociological Aspects - Александр Анатольевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
The State Program of Applied Researches “Development and a substantiation the system of measures for decreasing the risks and mitigation of consequences of natural and man-made emergency situations in Belarus” (“Decreasing the risks of emergencies”) for 2006-2010 alongside with other priority problems, provides the realization of research project “Development of effective methods of decreasing the risks of emergency situations on the basis of sociological study of their social preconditions”. It is being realized by Institute of sociology National Academy of Sciences of the Republic of Belarus together with the Gomel engineering institute for the Ministry of Emergency Situations of the Republic of Belarus.